Impelementasi Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan (PNPM-MP) terhadap Kesejahteraan Masyarakat Pesisir Desa Seluan Barat Kecamatan Bunguran Utara Kabupaten Natuna - Beri Tariyo; Almasdi Syahza; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT National Program for Community Empowerment in Rural Areas (PNPM-MP) is a national program launched by the government to improve the welfare of the community through community empowerment and community empowerment in an optimal and sustainable. The purpose of this program is to strengthen the economy with productive economic capital derived from such government activities to improve basic infrastructure or improving quality of life such as (health and education), Women's Savings and Loans business (SPP), and infrastructure development. Therefore, this study aims: 1) to describe the implementation of PNPM-MP in improving the well-being of coastal communities; 2) to determine the effect of PNPM-MP to the welfare of coastal communities. The experiment was conducted in the village Seluan Bunguran District of North West Natuna. The method used descriptive qualitative and quantitative descriptive. Number of samples 57 from 131 population. Purposive sampling using Solvin. The results showed the implementation of PNPM-MP has been going well as expected. This can be seen in the preparation of the views of the planning process, public sources of knowledge dissemination programs or PNPM-MP through socialization and community is involved in the implementation of the program. To stage the process of running the program effectively. While the evaluation of the program conducted; 2) Effect of PNPM-MP seen from the level of income affect the welfare of the community, because Chi Calculate > Chi Table.Keywords: Implementation of PNPM-MP, Welfare.